The role of arthroscopy in the management of adult elbow trauma - Maria Valencia; AM. Foruria (Journal of Experimental Orthopaedics, 2023)
Abstract Fractures around the elbow are often challenging to treat and in most cases require an extensive approach. Since the development of elbow arthroscopy, most authors have pointed out the potential advantages of a less invasive technique that can be useful for visualization and reduction of the articular fragments with an eventual percutaneous fixation. Arthroscopic techniques provide a limited exposure that may lead to a faster wound healing, lower rate of complications and thus, better recovery of range of motion. However, elbow arthroscopy is also a demanding technique, especially in a swollen and fractured joint, and it is not exempt of risks. The overall rate of complications has been rated from 1.5% to 11% and nerve injury rates from 1.26–7.5%. The objective of this review is to present the arthroscopic setup and general surgical technique for the management of elbow trauma and to define some clear indications. Patient positioning and operating room display is key in order to obtain success. In addition to the arthroscopic equipment, fluoroscopy is almost always necessary for percutaneous fixation and precise preparation is mandatory. In the last decade, literature regarding new portals or surgical tips for arthroscopic treatment of elbow fractures have been published. The main indications for fracture arthroscopic‐assisted fixation are those articular fractures involving the coronoid, distal humerus shear fractures in the coronal plane (trochlear and capitellum fractures) and, more controversially, those affecting the radial head. The treatment of these type of fractures all arthroscopically is exponentially demanding as it might also require ligament repair. For coronoid fractures, it can be useful in Morrey type II and III, and O´Driscoll anteromedial facet fractures associated to a posteromedial instability pattern that also require a repair of the LCL. Although excellent results have been published, comparative series are scarce. Radial head fractures can also be approached arthroscopically in simple non‐comminute fractures that can be fixed percutaneously. In conclusion, arthroscopy of the elbow is an excellent tool to better understand and visualize articular fractures of the elbow. However, despite the advances in surgical technique, whether it improves clinical and radiological results is still to be proven.